Satisfying experiences in old age attributes to successful aging - Espina, Ervina A.; Melgar, Ma. Isabel E. (Iloilo City University of the Philippines Visayas (UPV), 2010)
"This article examines satisfying experiences of old people which are considered attributes of successful aging. This qualitative study gathered data through the use of interviews with eighteen purposively selected participants: nine (9) males and nine (9) females, from Tacloban City, Leyte, and with ages ranging from 60-89 years. The findings highlighted six themes: presence of grandchildren, familial support, leisure and social engagements, receiving monetary entitlement, devotion and religious movement, and helping others. The various satisfying experiences of the participants indicated what they believed to be essential to successful aging. The study offers the idea that forming close social ties, acquiring a broad range of leisure and social activities, fortifying religious devotion, and strengthening familial bond are activities that should be pursued by the elderly since they highly value the relational quality of these experiences."
Keywords: Aging; Elderly; Successful aging